Harmonic current prediction by impedance modeling of grid-tied inverters: A 1.4 MW PV plant case study. (December 2017) - Pereira, H.A.; Freijedo, F.D.; Silva, M.M.; Mendes, V.F.; Teodorescu, R.
Highlights: Comparison of PWM, average and impedance models for harmonic current emission. A case study performed in a real 1.4 MW PV plant connected in a distributed system. Prediction of the PV plant harmonic current emission at the point of common coupling. Stress test is proposed to investigate the impact of the harmonic voltage phase angle. Abstract: Grid-tied inverters are the main responsible for the successful integration of photovoltaic (PV) plants in the power grid. Two important challenges are the integration of power plants based-inverters and their contribution to the power system quality. This work analyzes the features of inverter impedance models when used in harmonic integration studies. It is aimed to estimate the harmonic current contribution as a function of the background harmonic voltages components. Time domain simulations based on detailed and average models are compared with the impedance model developed in frequency domain. In grids with harmonic voltages, impedance models can predict the current distortion for all active power injection scenarios. Furthermore, measurements in a 1.4 MW PV plant connected in a distributed grid are used to validate the simulation based on impedance models during different power injections and harmonic voltage profiles. Results reinforce that impedance models can represent with relatively accuracy the harmonic current emitted by the PV plants at the point of common coupling (PCC). Lastly, a stress test is performed to show how a variation in the harmonic voltage phase angle impacts the PV plant harmonic emission.